Wpływ redystrybucji na wysokość świadczeń z polskiego bazowego systemu emerytalnego o zdefiniowanej składce - Owczarek, Joanna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2010)
In 1999, Poland implemented significant pension system reform in response to rising public pension expenditures and the threat of an unsustainable system. Th e reform has totally changed both the financing and pension formula. A generously defined benefit formula has been replaced with a multi -pillared defined contribution system. The reform was positively assessed by the public opinion, although replacement rates have been seriously cut. This acceptance was made possible mainly by introducing individual funded pension accounts convincing the participants that they owe their pension capital. Changes to the pension formula and diversified methods of financing reduced income redistribution within the system and the redistributive tools adopted in the pension mechanism. Lower replacement rates and benefits promised by the new system may cause huge demand for minimum pension guarantee payments in the future. This article describes the influence of pension reform on income transfers between different groups of its participants. It considers the direction and the degree of pension redistribution within both the old and the new mandatory pension system in Poland. It consists of four parts: The first is devoted to pension formula before and aft er the reform; the second presents and describes in detail redistributive elements used in Polish statutory pension system. Thirdly, various measures of income redistribution used for social security are enumerated. The final part examines the income redistribution between different groups of pensioners using the pension benefits, replacements rates and internal rates of return.